Effect of nitrogen and magnesium sulfate application on sugar beet yield and quality - Radosław Pogłodziński; Przemysław Barłóg; Witold Grzebisz (Plant, Soil and Environment, 2021)
Adequate nutrition of sugar beet with magnesium (Mg) and sulfur (S) has been assumed to be the key to increase fertiliser nitrogen (N) efficiency. This hypothesis was validated on two soils differing in textural class, i.e., sandy and loamy. The experiment consisted of three factors: (1) in-soil application of Kieserite (0, 24 kg Mg/ha); (2) foliar application of Epsom salt (0.2 kg Mg/ha); (3) N rates (0, 40, 80, 120, 160 and 200 kg N/ha). The following parameters were evaluated: (i) yield of storage roots (TY); (ii) qualitative features of storage roots, and (iii) yield of white sugar (WSY). Both yield characteristics, regardless on soil, were affected to a greater extent by in-soil than foliar MgS application. The highest increments of TY and WSY were obtained in 2016, a year with fewer favourable weather conditions and in soil with a wider Ca:Mg ratio. The greatest effect of Kieserite on TY and WSY was observed under low rates of applied N (up to 80 kg/ha). It can be concluded that the right nutrition of sugar beet with MgS in the early stages of sugar beet growth is the prerequisite of an effective N management on soils rich in mineral N.